A POLÍTICA DE INSERÇÃO DO BRASIL NA SOCIEDADE DA INFORMAÇÃO : uma avaliação política do Programa Sociedade da Informação (SOCINFO) - Pimenta, Márcia Teresa da Rocha (2014)
Political evaluation of the SOCINFO - Information Society Program. It analyzes the political, ideological, economic, social, cultural and institutional fundamentals that have conditioned the formulation process of the Brazilian information policy, having as empirical reference the Information Society Program, also known as Green Book. The study presents a critical approach of the State's actions, given the dictates of the neoliberalism, to disclose the apologetic discourse of the so-called "information society", in the Brazilian scenario. The approach about information and digital inclusion started up with the idolatry of the individuals towards the Technologies of Information and Communication TIC, resulting from the misleading possibilities of social inclusion, notably in countries with late and peripheral capitalism, as it is the case of Brazil. As we discuss the organic relationship between the State and capital, sustained by the neoliberalism, we come to the conclusion that the origin of the Brazilian information policy derived from the ideological option arisen out of the State-capital binomial, under the strong influence of the information fetishism and of the TIC present in the contemporary capitalism. Then, the SOCINFO has disclosed itself as another capitalist project for the adjustment of the Brazilian State to the political pressure of the hegemonic countries, which main goal was to insert the country in the globalized economy, this time, through the proudly nationalist discourse of the information society . For such, seven action lines presented in the Green Book have been analyzed, such as: Market, work and opportunities; Standardization of services for the citizenship; Education for the information society; Content and cultural identity; Government to everyone; R&D, key-technologies and relevant applications; and Advanced infrastructure and new services. At the stage of analysis of the related lines of action of the Program, our concern was to demystify concepts included in each of them that could represent the context of the dominant ideology. Finally, we have noted that the Information Society Program, in Brazil, was built not to promote the digital inclusion and the democratization of the information in the country, but to preserve and expand the capitalism, bearing in mind that its building blocks shaped the logic of the capitalist exploitation, thus favoring the interests of the dominant class, in detriment of those of our massacred working class.